Balance of MafB and PU.1 specifies alternative macrophage or dendritic cell fate. - Bakri, Y; Sarrazin, S; Mayer, U; Tillmanns, S; Nerlov, C; Boned, A; Sieweke, M (2005)
Macrophages and myeloid dendritic cells (DCs) represent alternative differentiation options of bone marrow progenitors and blood monocytes. This choice profoundly influences the immune response under normal and pathological conditions, but the underlying transcriptional events remain unresolved. Here, we show that experimental activation of the transcription factors PU.1 and MafB in transformed chicken myeloid progenitors triggered alternative DC or macrophage fate, respectively. PU.1 activation also was instructive for DC fate in the absence of cytokines in human HL-60 cell-derived myeloid progenitor and monocyte clones. Differentiation of normal human monocytes to DCs led to a rapid increase of PU.1 to high levels that preceded phenotypic changes, but no MafB expression, whereas monocyte-derived macrophages expressed MafB and only moderate levels of PU.1. DCs inducing levels of PU.1 inhibited MafB expression in monocytes, which appeared to be required for DC specification, since constitutive MafB expression inhibited DC differentiation. Consistent with this, PU.1 directly bound to MafB, inhibited its transcriptional activity in macrophages, and repressed its ability to induce macrophage differentiation in chicken myeloid progenitors. We propose that high PU.1 activity favors DCs at the expense of macrophage fate by inhibiting expression and activity of the macrophage factor MafB.